The EITC and maternal time use: More time working and less time with kids? - Jacob Bastian; Lance Lochner (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2020)
Parents spend considerable time and resources investing in their children's development. Given evidence that the Earned Income Tax Credit (EITC) affects maternal labor supply, we investigate how the EITC affects a broad array of time-use activities, focusing on the amount and nature of time spent with children. Using 2003-2018 time-use data, we find that federal and state EITC expansions increase maternal work time, which reduces time devoted to home production, leisure, and time with children. However, for children of all ages, almost none of the reduction comes from time devoted to investment activities, such as active learning and development activities.
Keywords: D13; H24; H31; H53; I31; I38; J13; J22; 330; EITC; tax policy; time use; child investment; female labor supply